The influence of price fairness and hedonic lifestyle on purchase decision. Brand image as a mediating variable on second-hand iphone - Lutian, Kristin; Afifah, Nur; Bagus Purmono, Bintoro; Ramadania, Ramadania; Hendri, M. Irfani (Institute of Computer Science (IOCS), 2024)
Smartphones are a technology that is developing very rapidly in Indonesia. Smartphones were once considered a luxury item, but as time goes by, smartphones have become an inseparable part of modern society's lifestyle which is very helpful in working. With various types of smartphones available, the iPhone is the choice of Indonesian people. The large number of second-hand iPhone users in Indonesia is caused by the behavior of consumers who want to use luxury goods at low prices. This research aims to determine the influence of price fairness and hedonic lifestyle on purchasing decisions and brand image as mediating variables on second-hand iPhones in Indonesia. This research uses quantitative descriptive research using a sample of 200 respondents who use second-hand iPhones in Indonesia who distributed questionnaires. The sampling technique uses a purposive sampling method, with the criteria being that respondents are aged 17 years and over and people who use second-hand iPhones. In this research, analysis and measurement used Structural Equation Modeling (SEM) with the statistical tool AMOS 24. The findings in this research show that price fairness and hedonic lifestyle have a positive and significant effect on purchasing decisions for second-hand iPhones in Indonesia. Brand image as a mediating variable in price fairness and hedonic lifestyle has a positive and significant effect on the decision to purchase a second-hand iPhone in Indonesia.